2021
DOI: 10.1038/s41467-021-24703-7
|View full text |Cite
|
Sign up to set email alerts
|

TEM8 marks neovasculogenic tumor-initiating cells in triple-negative breast cancer

Abstract: Enhanced neovasculogenesis, especially vasculogenic mimicry (VM), contributes to the development of triple-negative breast cancer (TNBC). Breast tumor-initiating cells (BTICs) are involved in forming VM; however, the specific VM-forming BTIC population and the regulatory mechanisms remain undefined. We find that tumor endothelial marker 8 (TEM8) is abundantly expressed in TNBC and serves as a marker for VM-forming BTICs. Mechanistically, TEM8 increases active RhoC level and induces ROCK1-mediated phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 57 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…Another novel target for ADC development has been TEM8, a transmembrane glycoprotein initially found to be a TEM but more recently also shown to be expressed widely in the tumour stroma across several human tumours [121][122][123]. The TEM8 targeting m825 [124] was developed into an ADC by conjugating it with MMAE via a cleavable linker.…”
Section: The Tme-a Promising Area For Adc Developmentmentioning
confidence: 99%
“…Another novel target for ADC development has been TEM8, a transmembrane glycoprotein initially found to be a TEM but more recently also shown to be expressed widely in the tumour stroma across several human tumours [121][122][123]. The TEM8 targeting m825 [124] was developed into an ADC by conjugating it with MMAE via a cleavable linker.…”
Section: The Tme-a Promising Area For Adc Developmentmentioning
confidence: 99%
“…TEM8/ANTXR1 is unique in its association with tumor vessels but not normal blood vessels (Chaudhary et al, 2012). TEM8/ANTXR1 has been described as a marker for pathological, tumor-associated angiogenesis, which promotes tumor growth and may mediate resistance to therapies targeting angiogenesis (Xu et al, 2021).…”
Section: Study Description Outcomesmentioning
confidence: 99%
“…Studies have demonstrated that TEM8/ANTXR1 is enriched in triple negative breast cancer (Xu et al, 2021), prostate cancer (Li et al, 2021a), gastric cancer (Li et al, 2021b;Sun et al, 2021), pancreatic cancer (Alcalá et al, 2019), angiosarcoma (Kusaba et al, 2021(Kusaba et al, ), colon cancer (Ł et al, 2021, and non-small cell lung cancer (NSCLC) (Gong et al, 2021). In multiple tumor types, upregulation of TEM8/ ANTXR1 is a negative prognostic indicator (Li et al, 2021a;Ł et al, 2021;Ding et al, 2021).…”
Section: Study Description Outcomesmentioning
confidence: 99%
See 2 more Smart Citations